Urbanization, food security and nutrition - Ruel, Marie T.; Garrett, J.; Yosef, S.; Olivier, M. (Springer, 2017)
For the first time in history, more than half of the world’s population lives in urban areas. This has profound implications for global trends in poverty, food security and nutrition and for global and local food systems. This chapter reviews the status of poverty, food security and malnutrition in urban compared to rural areas; provides an overview of the unique challenges and opportunities for urban dwellers to generate income and achieve food security and nutrition; and discusses the implications for urban programs, policies and research. Our review confirms that the location of poverty is rapidly shifting from rural to urban areas and that food insecurity and malnutrition in all its forms are highly prevalent among urban dwellers. Particularly alarming are the rapid rises in overweight and obesity in urban areas, while undernutrition and micronutrient deficiencies persist. Our review highlights critical gaps in knowledge and understanding of the distinctive factors and conditions that shape poverty, food security and nutrition in urban areas; it calls for new research to better document how food systems affect the nutrition transition, as well as urban diets and nutrition, and how, in turn, the food system could be leveraged to prevent future deterioration. We conclude that in order to counter the rising challenge of the nutrition transition and to achieve zero hunger and malnutrition, policymakers and programmers must be equipped with better data to design adequate programs and policies that: (1) support increased food availability and access of the urban poor to healthy, nutritious and safe foods and stimulate demand for healthy diets; (2) promote and facilitate physical activity; (3) promote and support urban agriculture and safe, affordable and nutritious street foods; (4) create income-generating opportunities for urban dwellers, including women, and use tailored and well-targeted social safety net programs as needed; (5) ease trade-offs for working women; and (6) improve access of poor urban dwellers to high-quality health care, water, sanitation, waste removal and electricity services.